KRISIS IDENTITAS REMAJA DALAM KARYA LUKIS - TEGUH EKO SAPUTRA, Drs. Erfahmi, M.Sn., Drs. Abd. Hafiz, M.Pd. (Universitas Negeri Padang, 2016)
The purpose of this final work making is visualizing the phenomena that occur in adolescence that's called identity crisis during the transition from adolescence into adulthood. It is stated in the works of contemporary painting . The embodiment of art ideas are created aftet doing an observation around the society. In the creation of the work . The author uses variety of tools and materials . Starting from acrylic paint , aerosol paint , pens , pencils and marker . The materials are canvas and wood . The author uses contemporary shades which in the work of art there are some rules that's omitted or ignored. Such as, not considering the social ethics and another ethical.The ten works of art that the author created are : 1) who I am 2) Appeal 3) When we grow 4) Drifting 5) The youth 6) Target 7)Fac_tor 8) Hope 9) Crisis of 21 10) Dilemma.Kata Kunci : Remaja, KrisisIdentitas, SeniLukisKontemporer